A two-dimensional carbon quantum dot / MoS2 nanosheet composite material and preparation method thereof
By adding carbon quantum dots to regulate its electronic structure during the synthesis of MoS2 nanosheets, the rapid, controllable and low-cost preparation of two-dimensional MoS2 nanosheets was achieved, and the 2H phase to 1T phase was successfully converted, solving the preparation problems and high conversion obstacles in the prior art.
Patent Information
- Application Number
- CN202310323702.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-28
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-03-28
AI Technical Summary
The prior art is difficult to quickly, controllably and at low cost to prepare two-dimensional MoS2 nanosheets, and realize the conversion of 2H phase to 1T phase, and common methods require strict experimental conditions.
By adding carbon quantum dots to assist in the in-situ synthesis of MoS2 nanosheets, the carbon quantum dots act as structural regulators to regulate the electronic structure of MoS2 nanosheets to achieve metastable phase change and promote the formation of two-dimensional materials.
It realizes the rapid, controllable and low-cost preparation of two-dimensional MoS2 nanosheets, and successfully realizes the conversion of 2H phase to 1T phase, which is suitable for industrial mass production.
Smart Images

Figure CN116443856B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of two-dimensional material synthesis, and in particular to a carbon quantum dot / MoS2 nanosheet composite material and a preparation method thereof. Background Art
[0002] Molybdenum disulfide (MoS2) is the most studied transition metal chalcogenide and is an ideal catalyst to replace platinum due to its low price, abundant resources, non-toxicity and high catalytic activity for hydrogen evolution reaction. Unlike bulk MoS2, nearly monolayer MoS2 nanosheets have attracted widespread attention due to their high specific surface area and surface activity. MoS2 mainly has two different crystalline phases: 2H phase and 1T phase, depending on the arrangement of S atoms, because the 4d orbital of Mo in 1T MoS2 is not fully filled. It is well known that the conductivity of 1T MoS2 (metallic conductor property) is one hundred times that of 2H MoS2 (semiconductor property), which makes it a promising alternative for catalytic water electrolysis to produce hydrogen. However, 1T MoS2 cannot be directly mined from natural ores and is difficult to produce on a large scale by common chemical or physical methods. To date, it has been reported that 1T MoS2 can be produced based on 2H MoS2 through conversion reactions triggered by electron beam, light irradiation and metal doping. In particular, achieving this phase transition via these experimental methods usually requires harsh experimental conditions, such as supercritical hydrothermal and high-risk reagents, to overcome the high conversion barrier of 2H MoS2 to 1T MoS2.
[0003] CN 104226337B discloses a graphene-loaded lamellar molybdenum disulfide nanocomposite and a preparation method thereof. The invention uses ammonium molybdate and thiourea as starting materials, and enables lamellar nano-molybdenum dioxide to be loaded on the surface of graphene oxide under hydrothermal conditions; after calcination, the lamellar molybdenum disulfide loaded on the graphene has a higher crystallinity, and the photocatalytic efficiency is more than 1.7 times that of commercial nano-titanium oxide. However, the thiourea used in the invention is decomposed into toxic gases such as hydrogen sulfide and ammonia through high temperature during the reaction process.
[0004] Carbon quantum dots have become a rising star in carbon-based nanomaterials due to their unique properties, such as sufficient active centers and abundant surface functional groups, and have attracted widespread attention in the electrocatalytic industry. Generally speaking, carbon quantum dots mainly refer to nanomaterials with a size less than 10 nm and composed of a carbon skeleton and surface-modified functional groups. The carbon skeleton is usually composed of sp 2 Hybridized CO, C=C, OC=O and graphitic carbon, or sp 2 and sp 3Amorphous carbon composed of mixed hybrids. In order to make carbon quantum dots have better properties and application prospects, researchers usually modify some functional groups on their surface, such as hydroxyl and carboxyl. The preparation process of carbon quantum dots is simple, low-cost, and stable. At the same time, they have excellent photogenerated electron transfer ability and are ideal electron acceptors and donors. In addition, carbon quantum dots have the characteristics of large specific surface energy and small size, which effectively inhibits the agglomeration of by-products and is conducive to the formation of nanosheets.
[0005] Therefore, there is an urgent need for a carbon quantum dot / MoS2 nanosheet composite material and a preparation method thereof to achieve the rapid, controllable, and low-cost preparation of two-dimensional MoS2 nanosheets and the transformation from 2H phase to 1T phase. Summary of the invention
[0006] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a carbon quantum dot / MoS2 nanosheet composite material and a preparation method thereof. The preparation method adds carbon quantum dots to assist in the in-situ synthesis of MoS2 nanosheets. During the preparation process, the carbon quantum dots act as structure regulators to regulate the electronic structure of the MoS2 nanosheets to achieve metastable phase transitions and promote the formation of two-dimensional materials. It can achieve rapid, controllable, and low-cost preparation of two-dimensional MoS2 nanosheets and realize the conversion from 2H phase to 1T phase.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] The first object of the present invention is to provide a carbon quantum dot / MoS2 nanosheet composite material and a preparation method thereof, wherein the preparation method is a carbon quantum dot-assisted preparation method, and the preparation method comprises the following steps:
[0009] S1. Ultrasonic dissolving a sulfonic acid precursor and trinitropyrene in a certain mass ratio in deionized water to obtain a mixed solution, reacting the solution in a reactor at a certain temperature for a certain time, filtering and dialyzing the initial product, and drying the initial product to obtain a solid powder of carbon quantum dots as sulfonic acid functionalized carbon quantum dots;
[0010] S2. Dissolve the sulfonic acid functionalized carbon quantum dots, Mo inorganic salt and S inorganic salt obtained in step S1 in deionized water, stir to obtain a uniformly mixed inorganic salt solution, react at a certain temperature in a reactor for a certain time, centrifuge with ethanol, wash, and vacuum dry to obtain a carbon quantum dot / MoS2 nanosheet composite material.
[0011] Furthermore, the reactor is a polytetrafluoroethylene reactor.
[0012] Furthermore, the mass ratio of the sulfonic acid precursor to trinitropyrene is 0.1-1.
[0013] Furthermore, in step S1, the sulfonic acid precursor is selected from one or more of sodium sulfite, 4-hydrazinobenzenesulfonic acid, 4-aminobenzenesulfonic acid, 4-hydroxybenzenesulfonic acid and 1-amino-2-naphthol-4-sulfonic acid.
[0014] Furthermore, in step S1, the amount of the sulfonic acid precursor added is 100-1000 mg.
[0015] Furthermore, in step S1, the reacting at a certain temperature in the reactor for a certain time is specifically transferring 20-60 ml of the mixed solution to a polytetrafluoroethylene high-pressure reactor for reaction at a heating temperature of 150-300° C. for a heating time of 6-30 h.
[0016] Furthermore, in step S1, the drying temperature of the drying primary product is not higher than 60°C.
[0017] Furthermore, in step S2, the inorganic salt of Mo and the inorganic salt of S are ammonium heptamolybdate and thiourea, respectively, with a mass ratio of 0.3-0.8 and a concentration range of 10-800 mmol / L.
[0018] Furthermore, in step S2, the amount of the sulfonic acid functionalized carbon quantum dots added to the inorganic salt solution is 10-300 mg.
[0019] Furthermore, in step S2, the stirring time is 0.5-2 h.
[0020] Furthermore, in step S2, the reacting at a certain temperature in the reactor for a certain time is specifically transferring 20-60 ml of the inorganic salt solution into the reactor, heating the temperature to 150-300° C., and heating the time to 6-30 h.
[0021] Furthermore, the above-mentioned reactor is a polytetrafluoroethylene reactor.
[0022] Furthermore, in step S2, the centrifugal separation speed is 8000-12000 rpm, and the centrifugal separation time is 1-20 min.
[0023] The second object of the present invention is to provide a carbon quantum dot / MoS2 nanosheet composite material and a preparation method thereof, wherein the carbon quantum dot / MoS2 nanosheet composite material is obtained by the above-mentioned preparation method, and the average thickness of the carbon quantum dot / MoS2 nanosheet composite material is not more than 20 nm.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1) The preparation method of the carbon quantum dot / MoS2 nanosheet composite material provided by the present invention is simple, easy, low-cost, mild in reaction, low in toxicity and simple in post-processing. At the same time, the prepared molybdenum disulfide has high yield, good quality and stable structure. The thickness of the MoS2 nanosheet synthesized in situ by adding carbon quantum dots can be adjusted. This method is suitable for industrial mass production of nano-sized carbon quantum dot / MoS2 nanosheet composite materials.
[0026] 2) The carbon quantum dot / MoS2 nanosheet composite material provided by the present invention has both 1T and 2H phase structures. 1T MoS2 cannot be mined directly from natural mines, and it is difficult to mass-produce by ordinary chemical or physical methods. So far, it has been reported that 1TMoS2 can be produced based on 2H MoS2 through conversion reactions triggered by electron beams, light irradiation, and metal doping. In particular, achieving this phase transition through these experimental methods usually requires harsh experimental conditions, such as supercritical hydrothermal and high-risk reagents, to overcome the high conversion barrier from 2H MoS2 to 1T MoS2. In order to improve this problem, carbon quantum dots are added during the synthesis of MoS2, and the amount of carbon quantum dots added, the reaction temperature, and the filling degree of the reactor are regulated to prepare a MoS2 heterojunction with coexistence of 1T and 2H phases.
[0027] 3) The carbon quantum dot / MoS2 nanosheet composite material provided by the present invention is a single layer or a few layers. Compared with bulk MoS2, the nearly single layer of molybdenum disulfide nanosheet has attracted widespread attention due to its high specific surface area and surface activity. The addition of carbon quantum dots in the inventive method is of great significance for opening the MoS2 interlayer spacing to form a nearly single layer nanosheet structure. The average thickness of the obtained carbon quantum dot / MoS2 nanosheet composite material can reach 2 nm.
[0028] 4) The preparation method of the carbon quantum dot / MoS2 nanosheet composite material provided by the present invention is to add carbon quantum dots to assist in the in-situ synthesis of the carbon quantum dot / MoS2 nanosheet composite material. The carbon quantum dots act as structure regulators during the preparation process to regulate the electronic structure of the carbon quantum dot / MoS2 nanosheet composite material to achieve metastable phase transition and promote the formation of two-dimensional materials, thereby achieving rapid, controllable, and low-cost preparation of two-dimensional MoS2 nanosheets and realizing the conversion from 2H phase to 1T phase. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a field emission transmission electron microscopy image of the sulfonic acid functionalized carbon quantum dots in Example 1 of the present invention, and the inset is a graph of the average size of the carbon quantum dots.
[0030] Figure 2 This is a transmission electron microscope image of the carbon quantum dot / MoS2 nanosheet composite material in Example 1 of the present invention.
[0031] Figure 3 1 is the XRD spectrum of the carbon quantum dot / MoS2 nanosheet composite material and the original 2H MoS2 in Example 1 of the present invention.
[0032] Figure 4 This is an atomic force microscope image of the carbon quantum dot / MoS2 nanosheet composite material in Example 1 of the present invention.
[0033] Figure 5 This is a scanning electron microscope image of MoS2 nanosheets synthesized without adding carbon quantum dots in the comparative example. DETAILED DESCRIPTION
[0034] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0035] Any features such as preparation methods, materials, structures or composition ratios that are not clearly described in this technical solution shall be deemed as common technical features disclosed in the prior art.
[0036] In the following examples, the raw materials used are all commercially available.
[0037] like Figure 1 As shown, it is a flow chart of the preparation method of the carbon quantum dot / MoS2 nanosheet composite material and its preparation method in the present invention, and the preparation method comprises the following steps:
[0038] S1. Ultrasonic dissolving a certain mass ratio of sulfonic acid precursor and trinitropyrene in deionized water to obtain a mixed solution, reacting at a certain temperature for a certain time in a polytetrafluoroethylene reactor, filtering and dialyzing the initial product, and drying the initial product to obtain a solid powder of carbon quantum dots as sulfonic acid functionalized carbon quantum dots;
[0039] S2. Dissolve the sulfonic acid functionalized carbon quantum dots, Mo inorganic salt and S inorganic salt obtained in step S1 in deionized water, stir to obtain a uniformly mixed inorganic salt solution, react at a certain temperature for a certain time in a polytetrafluoroethylene reactor, centrifuge with ethanol, wash, and vacuum dry to obtain a carbon quantum dot / MoS2 nanosheet composite material.
[0040] The applicant's conceptual process is as follows: 1T MoS2 cannot be mined directly from natural mines, and it is difficult to produce on a large scale through ordinary chemical or physical methods. So far, it has been reported that 1T MoS2 can be produced based on 2H MoS2 through conversion reactions triggered by electron beams, light irradiation and metal doping. In particular, achieving this phase change through these experimental methods usually requires harsh experimental conditions, such as supercritical hydrothermal and high-risk reagents, to overcome the high conversion barriers from 2H MoS2 to 1T MoS2. In order to improve this problem, carbon quantum dots are added during the synthesis of MoS2, and the amount of carbon quantum dots added, the reaction temperature, and the filling degree of the reactor are regulated to prepare a MoS2 heterojunction with coexistence of 1T and 2H phases, that is, by adding carbon quantum dots to assist in the in-situ synthesis of MoS2 nanosheets, the carbon quantum dots act as structural regulators during the preparation process, regulate the electronic structure of the MoS2 nanosheets to achieve metastable phase transition and promote the formation of two-dimensional materials, thereby achieving rapid, controllable, and low-cost preparation of two-dimensional MoS2 nanosheets and realizing the conversion from 2H phase to 1T phase. Compared with bulk MoS2, near-monolayer MoS2 nanosheets have attracted widespread attention due to their high specific surface area and surface activity. The addition of carbon quantum dots is of great significance for opening the MoS2 interlayer spacing to form a near-monolayer nanosheet structure. Example
[0041] This embodiment provides a carbon quantum dot / MoS2 nanosheet composite material, and the preparation method thereof comprises the following steps:
[0042] S1. Dissolve 500 mg of sodium sulfite and 200 mg of trinitropyrene in deionized water by ultrasonication to obtain a mixed solution, react in a polytetrafluoroethylene reactor at 160°C for 12 h, filter and dialyze the initial product, and dry the initial product at 60°C to obtain a solid powder of carbon quantum dots as sulfonic acid functionalized carbon quantum dots;
[0043] S2, dissolving the sulfonic acid functionalized carbon quantum dots (10 mg), ammonium heptamolybdate (18 mg) and thiourea (60 mg) obtained in step S1 in 6 mL of deionized water, stirring for 0.5 h to obtain a uniformly mixed inorganic salt solution, reacting at 180°C in a polytetrafluoroethylene reactor for 20 h, centrifuging with ethanol, wherein the centrifugal separation speed is 8000 rpm, and the centrifugal separation time is 10 min. Washing, vacuum drying, and obtaining a carbon quantum dot / MoS2 nanosheet composite material.
[0044] The obtained carbon quantum dots / MoS2 nanosheets composite material can be applied in the field of electrochemical hydrogen production.
[0045] The test analysis is as follows:
[0046] The sulfonic acid functionalized carbon quantum dots obtained in step S1 of Example 1 were observed using a field emission transmission electron microscope, and it can be seen that the average size of the carbon quantum dots is 2.74 nanometers. Figure 1 Illustration. The carbon quantum dots / MoS2 nanosheet composite material prepared in step S2 of this embodiment 1 was measured using a field emission transmission electron microscope. It can be seen that dense carbon quantum dots exist on the surface of MoS2 in the obtained product, which proves the successful synthesis of the carbon quantum dots / MoS2 nanosheet composite material. Figure 2 illustration. Figure 3 The XRD spectrum of the carbon quantum dots / MoS2 nanosheet composite material obtained in Example 1 shows that the characteristic peaks of the obtained product have a good agreement with the characteristic peaks of the standard card JCPDS No.037-1492, proving the successful synthesis of MoS2. At the same time, it can be seen from the figure that after the carbon quantum dots are introduced into the MoS2 nanosheets, the position of the main characteristic peak of the MoS2 nanosheets is shifted, indicating that the introduced carbon quantum dots can induce the MoS2 nanosheets to produce a metastable phase transition, see Figure 3 Illustration. Figure 4 As shown, the AFM image of the product obtained in step S2 of Example 1 was tested using an atomic force microscope, and it was found that the average thickness of the two-dimensional carbon quantum dot / MoS2 nanosheet composite material was 1.5~2 nm.
[0047] like Figure 5 As shown in the scanning electron microscope image, the MoS2 nanosheets synthesized without the addition of carbon quantum dots are very thick and do not form nanosheets, and have obvious stacking phenomenon.
[0048] Comparative Example
[0049] This comparative example is basically the same as the embodiment 1, except that:
[0050] In the synthesis of MoS2 material, sulfonic acid functionalized carbon quantum dots were not added to the inorganic salt solution, and finally a thicker MoS2 material was produced.
[0051] A method for rapidly synthesizing MoS2 materials:
[0052] Ammonium heptamolybdate and thiourea were dissolved in deionized water and stirred for 0.5 h to obtain a uniformly mixed colorless and transparent inorganic salt solution, which was reacted in a polytetrafluoroethylene reactor for 20 h. Finally, the solution was washed by ethanol centrifugation and dried in vacuum to obtain MoS2 material. Example
[0053] This embodiment provides a carbon quantum dot / MoS2 nanosheet composite material, and the preparation method thereof comprises the following steps:
[0054] S1. 100 mg of 4-hydrazinobenzenesulfonic acid and 500 mg of trinitropyrene were ultrasonically dissolved in deionized water to obtain a mixed solution, which was reacted at 160° C. for 20 h in a polytetrafluoroethylene reactor. The initial product was filtered and dialyzed, and the initial product was dried at 60° C. to obtain a solid powder of carbon quantum dots as sulfonic acid functionalized carbon quantum dots;
[0055] S2. Dissolve the sulfonic acid functionalized carbon quantum dots (10 mg), ammonium heptamolybdate (15 mg) and thiourea (30 mg) obtained in step S1 in 12 mL of deionized water, stir for 0.5 h to obtain a uniformly mixed inorganic salt solution, react at 180 ° C in a polytetrafluoroethylene reactor for 15 h, centrifuge with ethanol at a speed of 1000 rpm for 15 min, wash, and vacuum dry to obtain a carbon quantum dot / MoS2 nanosheet composite material. Example
[0056] This embodiment provides a carbon quantum dot / MoS2 nanosheet composite material, and the preparation method thereof comprises the following steps:
[0057] S1. 1000 mg of 1-amino-2-naphthol-4-sulfonic acid and 100 mg of trinitropyrene were ultrasonically dissolved in deionized water to obtain a mixed solution, which was reacted in a polytetrafluoroethylene reactor at 210° C. for 10 h, the initial product was filtered and dialyzed, and the initial product was dried at 60° C. to obtain a solid powder of carbon quantum dots as sulfonic acid functionalized carbon quantum dots;
[0058] S2. Dissolve the sulfonic acid functionalized carbon quantum dots (15 mg), ammonium heptamolybdate (80 mg) and thiourea (100 mg) obtained in step S1 in 24 mL of deionized water, stir for 0.5 h to obtain a uniformly mixed inorganic salt solution, react at 220 ° C in a polytetrafluoroethylene reactor for 24 h, centrifuge with ethanol, wherein the centrifugal separation speed is 12000 rpm, and the centrifugal separation time is 20 min. Wash and vacuum dry to obtain a carbon quantum dot / MoS2 nanosheet composite material.
[0059] The preparation methods in the above-mentioned embodiments 1 to 4 can prepare carbon quantum dots / MoS2 nanosheet composite materials, that is, carbon quantum dots-assisted synthesis of two-dimensional MoS2 nanosheets, and belong to the field of new two-dimensional material synthesis technology. The comparative example does not prepare a composite material containing carbon quantum dots, and the carbon quantum dots cannot play the role of a structural regulator during use, which is not conducive to promoting the formation of two-dimensional materials, and cannot induce MoS2 to achieve a phase transition from 2H to 1T. In the above-mentioned embodiment 1, carbon quantum dots are synthesized by molecular fusion method, and carbon quantum dots are used as auxiliary agents. Two-dimensional MoS2 nanosheets (carbon quantum dots / MoS2 nanosheet composite materials) with 1T and 2H phase coexistence are prepared in situ by a top-down synthesis strategy with inorganic salt solutions of molybdenum and sulfur at room temperature. The synthesis method of the above-mentioned embodiment is simple and easy to operate, mild in reaction, low in toxicity, and simple in post-processing. At the same time, the prepared molybdenum disulfide has high yield, good quality, and stable structure. This safe and low-cost in-situ induced phase change synthesis strategy is inspiring for the development of related heterostructures in electrocatalysis or phase changes of other TMDs materials for energy conversion systems.
[0060] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a two-dimensional carbon quantum dot / MoS2 nanosheet composite material, characterized in that: The preparation method comprises the following steps: S1. Ultrasonic dissolving the sulfonic acid precursor and trinitropyrene in deionized water to obtain a mixed solution, reacting in a reactor, filtering and dialyzing the initial product, and drying the initial product to obtain a solid powder of carbon quantum dots as sulfonic acid functionalized carbon quantum dots; S2, dissolving the sulfonic acid functionalized carbon quantum dots, Mo inorganic salt and thiourea obtained in step S1 in deionized water, stirring to obtain a uniformly mixed inorganic salt solution, reacting in a reactor, centrifuging with ethanol, washing, and vacuum drying to obtain a two-dimensional carbon quantum dot / MoS2 nanosheet composite material; The two-dimensional carbon quantum dot / MoS2 nanosheet composite material has both 1T and 2H phase structures; In step S1, the sulfonic acid precursor is selected from one or more of sodium sulfite, 4-hydrazinobenzenesulfonic acid, 4-aminobenzenesulfonic acid, 4-hydroxybenzenesulfonic acid and 1-amino-2-naphthol-4-sulfonic acid; In step S1, the drying temperature of the drying primary product is not higher than 60°C; The average thickness of the two-dimensional carbon quantum dots / MoS2 nanosheet composite material is 1.5~2 nm.
2. The method for preparing a two-dimensional carbon quantum dot / MoS2 nanosheet composite material according to claim 1, characterized in that: In step S1, the amount of the sulfonic acid precursor added is 100-1000 mg.
3. The method for preparing a two-dimensional carbon quantum dot / MoS2 nanosheet composite material according to claim 1, characterized in that: In step S1, the reaction in the reactor is specifically to transfer 20-60 ml of the mixed solution to the reactor for reaction, with a heating temperature of 150-300° C. and a heating time of 6-30 h.
4. The method for preparing a two-dimensional carbon quantum dot / MoS2 nanosheet composite material according to claim 1, characterized in that: In step S2, the inorganic salt of Mo is ammonium heptamolybdate, the mass ratio of ammonium heptamolybdate to thiourea is 0.3-0.8, and the concentration range is 10-800 mmol / L.
5. The method for preparing a two-dimensional carbon quantum dot / MoS2 nanosheet composite material according to claim 1, characterized in that: In step S2, the amount of the sulfonic acid functionalized carbon quantum dots added to the inorganic salt solution is 10-300 mg.
6. The method for preparing a two-dimensional carbon quantum dot / MoS2 nanosheet composite material according to claim 1, characterized in that: In step S2, the reaction in the reactor is specifically carried out by transferring 20-60 ml of the inorganic salt solution into the reactor, heating the mixture at a temperature of 150-300° C. for a heating time of 6-30 h.
7. The method for preparing a two-dimensional carbon quantum dot / MoS2 nanosheet composite material according to claim 1, characterized in that: In step S2, the centrifugal separation speed is 8000-12000 rpm, and the centrifugal separation time is 1-20 min.
8. A two-dimensional carbon quantum dot / MoS2 nanosheet composite material obtained by the preparation method as described in any one of claims 1 to 7.
Citation Information
Patent Citations
A kind of graphene supported flake layered molybdenum disulfide nanocomposite and preparation method thereof
CN104226337B
Nitrogen-and-sulfur-codoping-based graphene quantum dot material as well as preparation method and application thereof
CN108276996A
Preparation method and application of molybdenum disulfide-carbon quantum dot composite material
CN117839724A